Pediatric skull base tumors: Clinical features and surgical outcomes; a single center retrospective study with a review of literature - M. Grutza; P. Lenga; M. Issa; A. Seitz; F. Sahm; T. Milde; A.W. Unterberg; S.M. Krieg; A. El Damaty (Brain and Spine, 2024)
Objectives: Pediatric intracranial tumors, particularly at the skull base, are rare and present unique challenges to pediatric neurosurgeons and oncologists, owing to their complex anatomy and diverse histopathology. Robust evidence is still marginal concerning their clinical and surgical courses. Our aim is to describe our experience regarding surgical approaches, with special focus on surgical features, postoperative outcomes, adverse events as well as adjuvant therapeutic concepts. Methods: Patients aged <18 years undergoing skull base surgery between 2017 and 2023 at our institution were retrospectively enrolled. Patient demographics, tumor characteristics, surgical approach, pre -and postoperative clinical status and adjuvant therapy as well as overall and progression free survival were assessed. Results: Twelve children aged 6.1 ± 4.1 years were analyzed. There was a predominance of the female gender (7/12, 58.4%). Mean tumor diameter was 4.0 ± 2.9 cm. In three children the tumor was located suprasellar, temporobasal in one, adjacent to the cerebellar pontine angle in 4, clival in 3 and petroclival in 2 children. A subfrontal approach was performed in two patients, a subtemporal approach in one, a retrosigmoidal approach in 5 and in one patient two-staged approach; retrosigmoidal and later in a second operation pterional approach was conducted. One clival tumor was removed via an endonasal endoscopic approach and in another case via a transoral endoscopic approach. Gross total resection (GTR) and near total resection were achieved in 7 patients (58.3%). Tumor types included meningioma, clivus-chordoma, epidermoid cyst, anaplastic ependymoma, Ewing's sarcoma and Atypical Teratoid Rhabdoid Tumor (ATRT) as well as embryonal tumor with multilayered rosettes (ETMR). 4 patients (33.3%) died of disease due to tumor progression in average after 15 months. Hydrocephalus developed in two patients; a ventriculoperitoneal shunt was inserted in one patient, while an endoscopic third ventriculostomy (ETV) was performed in the other. Moreover, one child suffered from a residual neurological deficit at last follow-up evaluation. Adjuvant therapy protocols were applied in six patients (50.0%). Conclusion: Skull base tumors in children present a therapeutic challenge due to their rarity and unique pathological composition and can lead to considerable morbidity and mortality. An interdisciplinary approach involving neurosurgeons, pediatric oncologists and radiotherapists is mandatory to guarantee the best clinical course.